Childcare Use and Parents' Labour Supply in Australia - Lee, W; Kalb, G (My University, 2007)
Based on data which are representative of the Australian population in 2002, this paper first analyses the demand for and cost of formal and informal childcare for couple and sole parent families, shedding light on factors which affect the demand for childcare. The predicted demand of formal childcare and the predicted costs of informal childcare arising from these models are then used to impute total childcare costs at different levels of labour supply. Finally, the predicted total costs are incorporated in the estimation procedure of structural labour supply models for couple and sole parent families. By making several extensions to the methodology adopted in Doiron and Kalb (2005a), who estimated similar models based on 1996 Australian data and which this paper largely replicates in terms of methodology, it is found that the average elasticities of labour supply with regard to the cost of childcare are quite similar to the earlier estimates. The elasticities remain at the lower end of the range found in the international literature with the exception of the elasticities for sole parents with preschool children and/or on relatively low wages.
Melbourne Institute of Applied Economic and Social Research Working Paper Series
Keywords: Employment; Child Care; Employment -- Labour force participation; Health and wellbeing; Labour market; Health; Employment and unemployment